Strengthening Government and Community Institutions in Disaster Communication in Kesugihan Sub-District, Cilacap District: Lessons from the COVID-19 Pandemic - Ganjar Runtiko, Agus; Muslicha, Evawani; Santoso, Edi; Pangestuti, Sri; Sambodo, Herman (KnE Social Sciences, 2023)
The COVID-19 pandemic in Indonesia has entered its third year and seems to be nearing its end. The COVID-19 disaster provides many life lessons for society, nation, and state. One of the takeaways from the COVID-19 disaster is improving how humans communicate during a disaster. This paper is part of the research results during the response and recovery phases of the COVID-19 pandemic in the Kesugihan sub-district. This study interviewed leaders of government institutions and FGDs with community leaders in the Kesugihan sub-district, comprising 32 informants. The most important finding in the research is the importance of social capital in fostering solidarity so that cooperation is established between government agencies and community institutions in dealing with disasters and eliminating obstacles. Keywords: communication, disaster, community, government, COVID-19